2015
DOI: 10.1515/pjfns-2015-0022
|View full text |Cite
|
Sign up to set email alerts
|

Physico-chemical, Enzymatic, Mineral and Colour Characterization of Three Different Varieties of Honeys from Kashmir Valley of India with a Multivariate Approach

Abstract: The present study was undertaken to determine the physico-chemical properties (moisture content, reducing sugars, proline content, electrical conductivity, ash content, pH, titrable acidity, HMF, water activity, total soluble solids and total solids), enzymatic activity (diastase and invertase), colour characteristics (mmpfund, ABS 450 and CIE L * a * b * ) and mineral content (Cu, Mn, Fe, Zn, Pb and Cd) of three different varieties of honeys from Kashmir valley of India (acacia honey, pine honeydew and multi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
58
3
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(68 citation statements)
references
References 28 publications
5
58
3
2
Order By: Relevance
“…CH is known for its dark color like oak, heather, and pine honeys (Küçük et al, ). According to the results of a large number of studies, it is accepted that phenolic contents and antioxidant activities of dark colored honeys are higher when compared with light colored ones (Beretta et al, ; Bertoncelj, Doberšek, Jamnik, & Golob, ; Can et al, ; Holderna‐Kedzia & Kedzia, ; Nayik & Nanda, ). Various studies indicated that the color of honey could be determined by sensory and instrumental methods (Terrab, Díez, & Heredia, ).…”
Section: Resultsmentioning
confidence: 99%
“…CH is known for its dark color like oak, heather, and pine honeys (Küçük et al, ). According to the results of a large number of studies, it is accepted that phenolic contents and antioxidant activities of dark colored honeys are higher when compared with light colored ones (Beretta et al, ; Bertoncelj, Doberšek, Jamnik, & Golob, ; Can et al, ; Holderna‐Kedzia & Kedzia, ; Nayik & Nanda, ). Various studies indicated that the color of honey could be determined by sensory and instrumental methods (Terrab, Díez, & Heredia, ).…”
Section: Resultsmentioning
confidence: 99%
“…Some typical examples of storage may include conventional storage at home or refrigerated storage for the design and completion of a research study, such in our case. The higher antioxidant stability of dark colored honeys during storage is owed to their much higher pigment content compared to blossom honeys (Gheldof & Engeseth, ; Karabagias et al, ; Nayik & Nanda, ), comprising thus, an additional parameter of product's nutritional character during storage under refrigeration.…”
Section: Resultsmentioning
confidence: 99%
“…The great variability in honey composition and properties is owed to numerous factors including: botanical and geographical origin, bee species, harvesting season, processing conditions, beekeepers manipulations and practices, along with storage time, etc. (Chaikham, Kemsawasd, & Apichartsrangkoon, ; Gheldof, Wang, & Engeseth, ; Karabagias, Dimitriou, Kontakos, & Kontominas, ; Louppis, Karabagias, Kontakos, Kontominas, & Papastephanou, ; Nayik et al, ; Nayik, Dar, & Nanda, ; Nayik & Nanda, 2015a, , ; Wang, Gheldof, & Engeseth, ).…”
Section: Introductionmentioning
confidence: 99%
“…A principal component analysis (PCA) was conducted to evaluate the overall effect of the physicochemical (moisture content, ash content, a w , HMF, and pH) rheological (η [10C], η [15C], η [20C], η [25C], η [30C], G′ [1 Hz] and G″ [1 Hz]), and thermal (T g ) parameters, by a descriptive perspective. This methodology is applied to achieve a reduction of original data matrix while retaining the maximum amount of variability present in the data (Nayik and Nanda ). In a PCA analysis, when the components accumulate a high relative percentage of all variation (>70%), it can explain the variability shown between the samples (Mardia et al .…”
Section: Resultsmentioning
confidence: 99%